Zoom Utilization as an Online Learning Media during the COVID-19 Pandemic - Anna Gustina Zainal; Gita Hilmi Prakoso; Vito Frasetya; Ahmad Riza Faizal; Rudy Fardiyan; Fitri Juliana Sanjaya (Journal of Innovation in Educational and Cultural Research, 2022)
This research aims to analyze teachers’ digital literacy in the learning process at public elementary schools in Bengkulu, Indonesia. The focus is on teachers’ use of technological devices, especially their proficiency in operating, designing learning media, and utilizing digital media as a learning tool. This study employed qualitative research approach with descriptive type. The subjects were determined based on purposive with education background as the inclusive criteria. The data was collected using interview techniques where researchers were the primary instrument. The obtained data was analyzed through tabulation, coding, and conclusion withdrawal. Results showed that teachers firstly used technological devices as a learning tool due to the Covid-19 pandemic. They learnt to operate various device to transfer learning materials through visual, audio, and audiovisual methods. Teachers generally used smartphones and laptops, in which they are able to operate from the beginning to the end, including apps operation. Among the apps were Power Point, Canva, and Kinemaster with Zoom, Google Meets, Google Classroom, and WhatsApp as teaching platforms.